School-time's contribution to the physical activity level of children and fulfilment of national health recommendations for physical activity in Norway - Fredrik Kristiansen; Hilde Mikalsen; Pål Lagestad (Cappelen Damm Akademisk NOASP, 2021)
Physical activity (PA) among children is positively correlated to several positive health outcomes. Although school time constitutes an important arena for children's PA level because it includes all children, research in this area in Nordic countries remains limited. The aim of the present study is to investigate school-time's contribution to both children's total PA and fulfilment of health recommendations for PA. In total, 320 seventh-grade children volunteered to participate in the study, of which 291 provided valid accelerometer data and were included in the analyses. The results show that school time accounts for 30.6% and 26%, respectively, of boys' and girls' total moderate- and vigorous-PA (MVPA) during the week, and for 45.9% and 36.6%, respectively, of the MVPA that children need to fulfil the health recommendations. In addition, boys achieved significantly more MVPA than girls during school time, and school-time's contribution to the fulfilment of the health recommendations for PA was significantly greater among boys than girls. The findings indicate that PA in school time possesses an unrealized potential to substantially increase children's weekly PA. Possible strategies for increasing school-time's contribution to children's PA level, in general, and girls' PA level, in particular, are discussed.